Improving Teacher Performance Management - Yunggin, Yumeng (Proceedings Series of Educational Studies, 2024)
The general purpose of this study is to describe improving teacher performance management. The specific purpose is to describe: 1) teacher performance management planning, 2) teacher performance improvement management, 3) monitoring and evaluation of teacher performance management management and 4) problems found in teacher performance management management. The research method is qualitative descriptive and the data collection techniques are interviews, observations, and documentation. The subjects of the study are school principals and teachers. The results of the study show that planning, monitoring and evaluation of management in teacher performance runs effectively. However, based on the implementation of its management in improving teacher performance management, several problems were found, namely external problems and internal problems.